Moving outside the board room: A proof-of-concept study on the impact of walking while negotiating. - Marily Oppezzo; Margaret A Neale; James J Gross; Judith J Prochaska; Daniel L Schwartz; Rachael C Aikens; Latha Palaniappan (PLoS ONE)
Purpose Negotiation is a consequential activity that can exacerbate power differentials, especially for women. While traditional contexts can prime stereotypical gender roles and promote conditions that lead to performance differences, these can be mitigated by context shifts. This proof-of-concept study explores whether an easy-to-apply context shift, moving from seated indoors to walking outside, can help improve the quality of negotiated interactions. Here we examine walking's effects on negotiation and relational outcomes as well as experienced emotions, moderated by gender. Design Same-gender pairs were randomly assigned to either sitting or walking as either candidate or recruiter negotiating a job offer. Participants Eighty-one pairs of graduate students or community members participated: sitting pairs: 27 women, 14 men; walking pairs: 23 women, 17 men. Intervention Participants negotiated either while seated (across from each other) or walking (side by side along a path). Measures We measured: negotiation performance (total points) and outcome equity (difference between negotiating party points); subjective outcomes of positive emotions, negative emotions, mutual liking, and mutual trust. With mixed effects models, we tested main effects of condition, gender, and interaction of condition x gender. Results Relative to sitting, walking was associated with: increased outcome equality for women, but decreased for men (B = 3799.1, SE = 1679.9, p = .027); decreased negative emotions, more for women than men (IRR = .83, 95% CI:[.69,1.00], p = .046); and greater mutual liking for both genders (W = 591.5, p-value = 0.027). No significant effects were found for negotiation point totals, positive emotions, or mutual trust. Conclusion This study provides a foundation for investigating easy-to-implement changes that can mitigate stereotyped performance differences in negotiation.